(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. Keywords: Micrasterias torreyi Bail. var. nurulislamii Aziz var. nov.; Desmid; Green alga; Bangladesh. DOI: 10.3329/bjpt.v17i1.5399 Bangladesh J. Plant Taxon. 17(1): 109-111, 2010 (June)